2013
DOI: 10.4103/0974-2727.119843
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Challenges for Clinicians: Emergence of Methicillin-resistant Staphylococcus aureus, Vancomycin Resistance, and Current Treatment Options

Abstract: Gram-positive pathogens mainly, Staphylococcus aureus, Enterococcus and coagulase-negative Staphylococcus, are developing increasing resistance to glycopeptides that pose a problem in treating infections caused by these pathogens. Vancomycin is the treatment of choice in treating methicillin-resistant S. aureus (MRSA). Community-acquired MRSA is associated with infections in patients without recent history of hospital admission and without the classical risk factors for MRSA carriage (including healthcare pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 16 publications
(78 reference statements)
1
62
0
3
Order By: Relevance
“…While the development of vancomycin-resistant S. aureus has not been published in the spinal surgery literature, vancomycin-resistant S. aureus development has been found to be a concern when the MIC of vancomycin is below 4 mg/ml. 24 However, previously published studies have demonstrated that vancomycin can reach high concentrations well beyond the MIC needed to treat gram-positive organisms without systemic effects.…”
Section: Selective Pressures Concerns On Gram-negative Ssis and Vancomentioning
confidence: 99%
“…While the development of vancomycin-resistant S. aureus has not been published in the spinal surgery literature, vancomycin-resistant S. aureus development has been found to be a concern when the MIC of vancomycin is below 4 mg/ml. 24 However, previously published studies have demonstrated that vancomycin can reach high concentrations well beyond the MIC needed to treat gram-positive organisms without systemic effects.…”
Section: Selective Pressures Concerns On Gram-negative Ssis and Vancomentioning
confidence: 99%
“…However, vancomycin is not a benign therapy and the incidence of vancomycin-induced nephrotoxicity varies from 5%-35%. Most importantly, vancomycin-resistant strains of bacteria are increasing [5][6][7] and the excessive use of antimicrobial agents has worsened the susceptibility to vancomycin [8].…”
mentioning
confidence: 99%
“…he spread of multidrug-resistant Staphylococcus aureus strains in hospitalized patients and other individuals without health care-related risk factors raises alarming concerns in various countries and clinical settings due to the increasing likelihood of treatment failures and ensuing morbidity and mortality (1)(2)(3). In addition, the ability of S. aureus to sojourn and thrive intracellularly, well described in in vitro and in vivo models (4-7) and also documented in human infections, is considered to play a critical role in their persistent and recurrent character (8)(9)(10).…”
mentioning
confidence: 99%